Mild and Effective Polymerization of Dopamine on Keratin Films for Innovative Photoactivable and Biocompatible Coated Materials. Issue 8 (27th May 2018) - Posati, Tamara; Ferroni, Claudia; Aluigi, Annalisa; Guerrini, Andrea; Rossi, Francesca; Tatini, Francesca; Ratto, Fulvio; Marras, Emanuela; Gariboldi, Marzia Bruna; Sagnella, Anna; Ruani, Giampiero; Zamboni, Roberto; et al.
Abstract: Mussel‐inspired polydopamine (PD) coating represents a promising route for constructing functional materials and finely tuning or completely changing their surface properties. In this work, a mild and effective method to realize the deposition of PD on keratin‐based films is reported. Reactive oxygen species (ROS), generated by keratin films doped with a photosensitizer, e.g., Azure A (AzA), upon UV–vis and vis‐near IR irradiation, are exploited to obtain the PD coating. Interestingly, the use of vis‐near IR irradiation leads to an increased production of ROS by AzA resulting in a greater PD deposition. Compared to uncoated keratin films, the PD‐keratin coated materials show a granular but homogeneous surface and an increased hydrophilicity, maintaining the ROS generation ability of AzA. This work demonstrates a useful method to effectively and rapidly functionalize with PD materials that are sensitive to temperature, pH and UV light, such as keratin. The proposed strategy allows obtaining new multifunctional biomaterials of potential interest in tissue engineering and drug delivery; in particular, the use of PD‐keratin films for near IR laser bonding of ophthalmic tissue, which is a representative case in wound healing purpose, is shown. Abstract : An effective polydopamine (PD) coating on keratin film is made by using mild vis‐near IR irradiation. Biocompatible PD‐keratin coated films for laser‐assisted welding or soldering of ophthalmic tissue are obtained, paving the way for the preparation of new keratin‐based multifunctional materials of potential interest in tissue engineering and drug delivery fields.